2002
DOI: 10.1161/01.atv.0000043664.48689.7f
|View full text |Cite
|
Sign up to set email alerts
|

PlAPolymorphism of Integrin β3Differentially Modulates Cellular Migration on Extracellular Matrix Proteins

Abstract: Objective-Cell migration is central to multiple physiological and pathologic processes and involves interactions between integrins on the cell surface and the extracellular matrix. The Leu33Pro (Pl A ) polymorphism of integrin ␤ 3 has been reported to be associated with a greater rate of restenosis after angioplasty, a process involving endothelial and smooth muscle cell migration. We have addressed the possibility that the Leu33Pro polymorphism could modify the migratory behavior of Chinese hamster ovary (CHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 35 publications
1
24
0
1
Order By: Relevance
“…JAM-A regulates ␣ v ␤ 3 -dependent MAPK activation It is well documented that activation of ␣ v ␤ 3 leads to MAPK activation and endothelial cell migration (Camenisch et al, 2002;Degryse et al, 2001;Sajid et al, 2002). Because JAM-A overexpression leads to HUVEC migration, we thereby reasoned that JAM-A might also be involved in MAPK activation.…”
Section: Jam-a-induced Migration Is Specific To Vitronectinmentioning
confidence: 97%
“…JAM-A regulates ␣ v ␤ 3 -dependent MAPK activation It is well documented that activation of ␣ v ␤ 3 leads to MAPK activation and endothelial cell migration (Camenisch et al, 2002;Degryse et al, 2001;Sajid et al, 2002). Because JAM-A overexpression leads to HUVEC migration, we thereby reasoned that JAM-A might also be involved in MAPK activation.…”
Section: Jam-a-induced Migration Is Specific To Vitronectinmentioning
confidence: 97%
“…The protein carrying the Pl A2 allele has been shown to have increased and more stable interactions with fibrinogen, 35 enhanced platelet aggregability and thrombin generation, 36 -38 and enhanced cell migration. 39 Further, the Pl A2 allele has been associated with coronary thrombosis, 40,41 stroke, 42,43 and myocardial infarction. 44,45 Studies of ITGB3 polymorphisms and whole blood serotonin in patients with cardiovascular diseases and controls will be required to evaluate whether altered serotonin levels mediate the association between Pl A2 and cardiovascular phenotypes.…”
mentioning
confidence: 99%
“…β3 subunit also is a part of other integrins. One of them is αIIbβ3 integrin, involved in the process of platelet aggregation [31]. One common polymorphism in the gene sequence of β3 subunit (1567 T>C) was found to increase the subunit affinity to ligands and could influence the platelet interaction, as well as the adhesion process during implantation.…”
Section: Overview Of Human Embryo Implantation Stages Adhesion Glycomentioning
confidence: 99%
“…The impact of increased platelet activity on implantation process is particularly embarrassed, because investigated polymorphism A1/A2 concerns beta3 subunits of platelet integrin alphaIIb/beta3, which is also part of integrin αvβ3, related with embryo adhesion to endometrium [78]. An in vitro investigation has found that changes in the peptide structure of beta3 subunit have had influence on the receptor activity to its ligandsosteopontin and vitronectin [31]. Sajid et al [31] established that cell lines which expressed alphaV/beta3 receptor with PL A1/A2 had an enhanced haptotactic migratory response to vitronectin and osteopontin.…”
Section: Pl A1/a2 In Integrin Beta 3 Platelet Activity and Adhesion Pmentioning
confidence: 99%
See 1 more Smart Citation